How to Measure Globalisation? A New Globalisation Index (NGI) - Petra Vujakovic (Austrian Institute of Economic Research (WIFO), 2009)
With its 21 variables, the new composite globalisation index presented in this paper accounts for the multidimensionality of this phenomenon instead of relying purely on economic indicators. As compared to other existing globalisation indices, three major innovations are introduced: First, five variables that have until now not been used in globalisation indices enter the calculations. Second, geographical distances between countries are incorporated into the index in the trade variable, so as to account for the distinction between globalisation and regional integration. A final innovation is a methodological one, which concerns the use of a statistical method (principal component analysis) to form sub-indices according to the statistical features of the variable structure. A control for country size is employed for significantly affected variables, as was done in some other globalisation indices before. The final index contains 70 countries and covers the period of 1995 to 2005.
Keywords: 330; globlisation; openness of economies; growth and development; measurement of openness; integration; globalisation; Globalisierung; Messung; Wirtschaftsindikator; Welt